Characterization of Two Wheat-Derived Glycoside Hydrolase Family-10 Xylanases Resistant to Xylanase Inhibitors. (5th April 2022) - Liang, Fangfang; Mo, Yi; Shah, Suleman; Xie, Ying; Mehmood, Arshad; Jiang, Hesheng; Guo, Yafen
Abstract : Xylanase inhibitors inhibit the activities of microbial xylanases and seriously compromise the efficacy of microbial xylanases added to modify cereals. Cereal endogenous xylanases are unaffected by these xylanase inhibitors, but little information is available regarding their effects in improving cereal quality, a neglected potential application. As a strategy for circumventing the negative effects of xylanase inhibitors, the objective of this study was to use genetic engineering to obtain sufficient amounts of active endo-1, 4- β -D-xylanase from wheat to analyze the characteristics of its structure. The endo-1, 4- β -D-xylanase from wheat was heterologously expressed. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), western blotting, MALDI-TOF/TOF (MS) analyses, and enzyme activity determination confirmed 2 active endo-1, 4- β -D-xylanases (EXY3 and EXY4) were successfully obtained. The molecular weights (MW) and isoelectric point (pI) of EXY3 were 36.108 kDa and 5.491, while those of the EXY4 protein were 41.933 kDa and 5.726. They both contained the same catalytic domain of GH10 xylanases from G266 to V276 and have the same catalytic site, Glu273. They shared the same putative N-glycosylation sites (N62-T63-S64 and N280–V281–S282) and 3 putative O-glycosylation sites (Ser8, Ser9, and Thr21), but EXY4 had an additional O-glycosylation site (Thr358). EXY3 was smaller than EXY4 by 51 amino acids because of a nonsense mutation and premature termination. They both had the 8-fold beta/alpha-barrel (TIM-barrel) fold. The specific activities of EXY3 and EXY4 were 152.0891 and 67.2928 U/mg, respectively. This work demonstrates a promising way to obtain wheat xylanases by genetic engineering; the properties of the enzymes indicate their potential application in cereal-based industries.